Micronutrient dietary patterns associated with type 2 diabetes mellitus among women of the E3N‐EPIC (Etude Epidémiologique auprès de femmes de l'Education Nationale) cohort study: 国家妇女教育改革计划(E3N‐EPIC)队列研究中女性2型糖尿病患者相关的微量营养物质饮食模式. Issue 8 (23rd March 2018) - Mancini, Francesca Romana; Dow, Courtney; Affret, Aurélie; Rajaobelina, Kalina; Dartois, Laureen; Balkau, Beverley; Bonnet, Fabrice; Boutron‐Ruault, Marie‐Christine; Fagherazzi, Guy
Abstract: Background: Micronutrients play a key role in type 2 diabetes mellitus (T2DM), but methodological difficulties arise from their collinearity and interdependencies with foods. The aim of the present study was to identify micronutrient dietary patterns in the E3N‐EPIC (Etude Epidémiologique auprès de femmes de l'Education Nationale) cohort and to investigate their association with risk of T2DM. Methods: Principal component analysis was used to identify micronutrient patterns among 71 270 women from the E3N‐EPIC cohort. Associations between micronutrient patterns and risk of T2DM were quantified by hazard ratios (HRs) and 95% confidence intervals (CIs) from Cox proportional hazards regression models, adjusted for potential confounders. Results: Six micronutrient patterns were identified explaining 78% of the total variance in micronutrient intake. A positive association was found between T2DM and a pattern highly correlated with intake of vitamins B2 and B5 (HR 1.34; 95% CI 1.16–1.56). Similarly, a positive association was found with a pattern characterized by high intakes of vitamin B12 and retinol, and a low intake of vitamin C (HR 1.30; 95% CI 1.15–1.48). An inverse association was observed between T2DM and another two patterns: one correlated with magnesium and vitamin B3 (HR 0.75; 95% CI 0.66–0.86), and the other correlated with manganese intake (HR 0.82; 95% CI 0.72–0.94). Conclusions: The findings of the present study identify micronutrients that have an effect on the risk of T2DM, and enable better understanding of the complexity of the diet when investigating the association between micronutrients and T2DM. Abstract : Highlights This study shows how the use of micronutrient patterns enables investigation of the association between diet and type 2 diabetes mellitus (T2DM), explaining the complexity of the diet. The results suggest a protective effect of vitamins C and B3, magnesium, and manganese against T2DM. A positive association was found between the intake of vitamins B2, B12, and retinol and the risk of T2DM.